Impact of Technical Vocational Training on Unemployment Free Schools and Vocational Trainees - JAHANIAN , Ramezan; RAHELEH , Salehi (Asian Journal of Empirical Research, 2013)
The training of skilled and efficient manpower is one of the sustainability issues of development indicators. One way to achieve this goal due is to increase level of knowledge and training efficient manpower. The purpose of the present study is to determine the effect of vocational training on unemployment of trainees in free vocational schools. This study is a quasi-experimental, single group with pre-test and post-test. The population is consisting of trainees and free vocational schools. Sample of 220 individuals was selected randomly phased. Data collection questionnaire that its validity approved by using the 20 vocational training experts and the final has been estimated about 0.78 by using Cranach’s alpha coefficient. The findings indicated that vocational education have been effective in reducing the rate of unemployment of practitioners and there are differences between men and women about impact of education on reducing unemployment, so that the fell rate of unemployment in men was higher than women.